Investigating the elimination of dormancy and germination power of rice varieties under artificial storage in response to different temperatures - Nesar Ahmad Qasani; Farshid Ghaderi-Far (Genius Journals, 2022)
When the seeds of the plants had harvested, they are not planted immediately and are kept in storage for some time. Storage has positive and negative effects on the elimination of the dormancy and germination of different plants. Therefore, a study has carried out with the aim of investigating the elimination of dormancy and the germination power of rice varieties under artificial storage in response to different temperatures. In the treatments of zero (control) to eight days artificial aging on the germination of rice varieties AHS, DAH and DBC In response to the temperatures of 15, 20, 25, 30 and 35oC, with the help of thermal time model, it was done in the agriculture laboratory of Gorgon University of Natural Resources and Agricultural Sciences in 2019. Accelerated aging test has used in artificial storage. So that the seeds of AHS, DAH and DBC rice cultivars were kept for zero (control), one, two, three, four, six and eight days of artificial deterioration at a temperature of 45oC and a relative humidity of 100%. After that, the germination test of artificially aging seeds of rice cultivars has studied at temperatures of 15, 20, 25, 30 and 35oC. The results of this research showed that the germination percentage of rice cultivars in all treatments of artificial storage at 15oC was low. With the increase in temperature during artificial storage, the germination percentage of these cultivars increased. Additionally, with the increase of artificial storage treatments, it has observed that the percentage of germination decreases among all rice cultivars, and this decrease was evident at lower temperatures, therefore germination stopped in all cultivars of AHS, DAH and DBC in eight days of artificial aging
Keywords: Seed Dormancy; Seed Vigor; Seed Germination